Enteroviral Pathogenesis of Type 1 Diabetes: The Role of Natural Killer Cells - Nekoua, Magloire Pandoua (Microorganisms, 2020)
Enteroviruses, especially group B coxsackieviruses (CV-B), have been associated with the development of chronic diseases such as type 1 diabetes (T1D). The pathological mechanisms that trigger virus-induced autoimmunity against islet antigens in T1D are not fully elucidated. Animal and human studies suggest that NK cells response to CV-B infection play a crucial role in the enteroviral pathogenesis of T1D. Indeed, CV-B-infected cells can escape from cytotoxic T cells recognition and destruction by inhibition of cell surface expression of HLA class I antigen through non-structural viral proteins, but they can nevertheless be killed by NK cells. Cytolytic activity of NK cells towards pancreatic beta cells persistently-infected with CV-B has been reported and defective viral clearance by NK cells of patients with T1D has been suggested as a mechanism leading to persistence of CV-B and triggering autoimmunity reported in these patients. The knowledge about host antiviral defense against CV-B infection is not only crucial to understand the susceptibility to virus-induced T1D but could also contribute to the design of new preventive or therapeutic approaches for individuals at risk for T1D or newly diagnosed patients.